1988
DOI: 10.1021/ac00160a010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of partition coefficients from surface acoustic wave vapor sensor responses and correlation with gas-liquid chromatographic partition coefficients

Abstract: Surface acoustic wave (SAW) devices coated with a thin film of a stationary phase sense chemical vapors In the gas phase by detecting the mass of the vapor that distributes Into the stationary phase. This distribution can be described by the partition coefficient. An equation is presented that allows partition coefficients to be calculated from SAW vapor sensor frequency shifts. The experimental responses of fluoropolyd-coated 158-MHz dual delay line SAW vapor sensors are converted to partition coefficients by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 245 publications
(138 citation statements)
references
References 21 publications
3
134
0
1
Order By: Relevance
“…Temperature compensation, if perfect (which it never is) only compensates for the frequency drift of the bare devices. Thermal expansion of the polymer on a vapor sensor also induces a temperature drift which remains uncompensated, and the sorption of vapors is highly temperature dependent (17). Therefore, we find that little is lost by separating the reference and sensor chips, and much is gained by actively thermostatting the sensors.…”
Section: Lb Films On Resonatorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Temperature compensation, if perfect (which it never is) only compensates for the frequency drift of the bare devices. Thermal expansion of the polymer on a vapor sensor also induces a temperature drift which remains uncompensated, and the sorption of vapors is highly temperature dependent (17). Therefore, we find that little is lost by separating the reference and sensor chips, and much is gained by actively thermostatting the sensors.…”
Section: Lb Films On Resonatorsmentioning
confidence: 88%
“…This consideration demands that selectivity be achieved, a topic not considered in this paper. Selectivity with SAW resonators will be achieved by the same methods used with SAW delay lines and quartz crystal microbalances, namely: the development of selective sorbent materials, the use of sensor arrays with pattern recognition, and pre-separation or pre-concentration methods (2)(3)(4)(5)(6)(7)(8)17,18,(32)(33)(34)(35). Thus the requirements of real world applications will be met by integrating individual SAW vapor sensors into complete detection systems.…”
Section: Lb Films On Resonatorsmentioning
confidence: 99%
“…In terms of the (dimensionless) partition coefficient of the coating/analyte pair in a given fluid environment, the variation of the sensor's mass is given by [20] (10) in which is the sensitive coating thickness, the coated surface area of the microcantilever, the analyte concentration in the fluid (mass per unit volume), and the partition coefficient is a measure of the distribution of the analyte between the sorbed phase and the surrounding medium. Then, under the assumption , the sensor sensitivity (frequency shift per unit analyte concentration) due to analyte sorption reduces to the following linear relationship between sensitivity and the ratio of coating volume to the microstructure volume : (11) Here is the mass density of the beam's substrate material.…”
Section: A Sensor Sensitivitymentioning
confidence: 99%
“…Accordingly, a number of synthetic materials have been prepared and investigated as sensor phases, most of which incorporate hexafluoroisopropanol moieties as the hydrogen-bond acidic group. [28][29][30][31][32][33][34][35][36][37][38][39] A study several years ago compared the hydrogen-bond acidities of several propyl-or allylsubstituted bisphenol structures using inverse gas chromatography and LSERs. 40 It was shown that fluorinated bisphenol-A structures were substantially more hydrogen-bond acidic than non-fluorinated analogs; fluorination improved sorption of basic compounds by factors of 100 or more.…”
Section: Figure 2 Four Examples Of Sorbent Polymers Prepared By Hydrmentioning
confidence: 99%
“…28,29,41 Figure 5 shows the calibration curves for SAW sensors coated with BSP3, fluoropolyol (FPOL), and polydimethylsiloxane (PDMS) when tested against dimethyl methylphosphonate, a nerve-agent simulant. FPOL is a sensor coating for nerve agents described in the past, 26,27,33,42 and PDMS serves as an example of a sorbent polymer lacking functionalities designed for sorption of basic vapors. Signals of greater than 20,000 Hz are observed at a concentration of only 8 mg/m 3 using BSP3.…”
Section: Figure 3 Examples Of Monomers Used In Hydrosilylation Polymmentioning
confidence: 99%